SUPPLY AND DEMAND FACTORS OF THE STATE AND BUSINESS ON PUBLIC AND PRIVATE PARTNERSHIP - T. V. Tischenko (Вестник университета)
The subject of the study is public–private partnership (hereinafter – PPP) mechanisms in the modern economy of the Russian Federation. The article considers economic factors affecting the demand for PPP mechanisms in Russia from the state and business. The paper carries out a comparative assessment of the supply and demand of PPP and alternative mechanisms of interaction between the state and business. The study reveals that PPP does not have significant advantages in comparison with traditional public procurement or leasing. According to the results of the study, the author makes a forecast that in the near future we should expect a significant reduction in the volume of private and public co-financing of projects implemented on the basis of PPP. Assumption by state additional obligations to finance projects in the absence of budget restrictions can increase the demand for PPP on the part of business.